Is Quality of Life Better in Hemophilia Patients with or Without Prophylactic Treatment? Using Haemo-SYM to Answer the Question - Catalina GURAN; Mieta-Gabriela HATEGAN; Dacian Nicolae OROS; Despina CALAMAR-POPOVICI; Marioara IONITA HORTENSIA; Claudiu IONITA; Florica GHILEZAN; Ioana IONITA (Documenta Haematologica)
Hemophilia A is a bleeding disorder that is caused by a clotting factor VIII deficit. For years the research in Hemophilia was focused on new therapies, but since novel treatments brought a longer span of life for patients, the question of how greatly these treatments improved patients QoL arose. In Romania prophylactic treatment has been approved only in 2017. Until then our main focus was the life span of patients, but since the introduction of the prophilactic program we started to ask ourselves the same question. Therefore we collected data from 100 patients, 50 with prophylactic treatment and 50 without prophylactic treatment and applied the Haemo-SYM questionnaire and a self-evaluation tool. We found that QoL life has been improved slightly by the recent introduction of prophylaxis in our country and that the Haemo-SYM has proven once again as a useful tool in assessing QoL.